Mengenal Golongan Darah: Pengabdian Edukasi dan Pemeriksaan di Sekolah Menengah Pertama Negeri 12 Denpasar - Yuliyatni, Putu Cintya Denny; Putri, Pande Putu Ayu Rissa Cempaka; Wisnawa, I Nyoman Dharma; Ariawan, I Made Dwi; Sutarsa, I Nyoman; Sawitri, Anak Agung Sagung (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2025)
Background: The Ministry of Home Affairs of the Republic of Indonesia stated that only 14% of the population have reported their blood type in their civil identification, while the rest have either not reported it or are not unaware of their blood type. The majority of the population does not yet understand the importance of knowing their blood type, particularly in the context of healthcare. Purpose: This community service activity aimed to enhance the knowledge and awareness of junior high school (SMP) students in Denpasar regarding the importance of knowing their blood type as part of personal identity and preparedness in medical situations. Method: The activity was carried out through interactive education about the blood type system and its significance in healthcare, as well as direct blood type screening by a medical team. Participants included 7th-grade students, school organization members, and teachers who had not previously known their blood type. Result:The results showed that the majority of students had blood type O (48.69%) and were Rhesus positive (99.48%). The activity also demonstrated high enthusiasm among students and an increased understanding of the blood type system, reflected in the improvement of the average pre-test and post-test scores from 3.49 to 4.04. Conclussion:Through this activity, it is expected that students can become health literacy agents in their schools and communities.